ANALISIS SISTEM INFORMASI AKUNTANSI DAN SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG PADA TOKO CAMPLADEAN MANADO - Otinur, Faujan; Pangemanan, Sifrid S.; Warongan, Jessy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The accounting information system and the system of Internal control is a component that collect, classify, process, analyze and combine the relevant financial information for decision making the outside parties (suc as Government, community, investors, and creditors) parties in (especially management). Campladean Manado is a merchant selling sports equipment with various brands and types of goods so that it has a stockpile of goods quite a lot. This research aims to analyze accounting information systems inventory and enacted on Campaldean Manado. This research uses descriptive research method. Research results showed the accounting information system on Campladean Manado are still using manual systems of internal control systems but very helping and supporting accounting information systems in Manado in Campladean minimize the occurrence of errors in system of inventory items.Keywords: Accounting information systems, Interalcontrol systems supplies.